Natural dolomitic limestone-catalyzed synthesis of benzimidazoles, dihydropyrimidinones, and highly substituted pyridines under ultrasound irradiation - Godugu, Kumar; Yadala, Venkata Divya Sri; Pinjari, Mohammad Khaja Mohinuddin; Gundala, Trivikram Reddy; Sanapareddy, Lakshmi Reddy; Nallagondu, Chinna Gangi Reddy (Beilstein Journal of Organic Chemistry, 2020)
Natural dolomitic limestone (NDL) is employed as a heterogeneous green catalyst for the synthesis of medicinally valuable benzimidazoles, dihydropyrimidinones, and highly functionalized pyridines via C–N, C–C, and C–S bond formations in a mixture of ethanol and H2O under ultrasound irradiation. The catalyst is characterized by XRD, FTIR, Raman spectroscopy, SEM, and EDAX analysis. The main advantages of this methodology include the wide substrate scope, cleaner reaction profile, short reaction times, and excellent isolated yields. The products do not require chromatographic purification, and the catalyst can be reused seven times. Therefore, the catalyst is a greener alternative for the synthesis of the above N-heterocycles compared to the existing reported catalysts.
Keywords: benzimidazoles; dihydropyrimidinones; highly substituted pyridines; natural dolomitic limestone; ultrasound irradiation